GAMBARAN TINGKAT STRES MAHASISWA PRODI D III KEPERAWATAN SEMESTER AKHIR SEHUBUNGAN DENGAN PADATNYA PERKULIAHAN DAN PEMENUHAN TUGAS AKHIR DI AKADEMI KESEHATAN RAJEKWESI BOJONEGORO TAHUN 2017 - Safitri, Aprilia Devi; Maftukhin, Ahmad; Afandi, Agus Ari (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Stress is a non-specific body response to each of the load demand on it. The stress experienced by student during college is very possible given the high complexity of the problem encountered. This study aims to determine the level of stress D3 Nursing students final study in relation to the density of lectures and fulfillment of the task end of 2017. This research uses descriptive methode, with the entire student population at the end of the academic year 2016/2017, many as 97 people while the sample is 97 people, with total sampling technique. How to collect data with questionnaires which then processed by editing, coding, scoring, tabulation, that is presented in the form of frequency tables in confirmation with the precentage and narration. The result of the study of 97 respondents, less than most respondent that many as 47 students (48,5%) experienced mild stress levels. The conclusion is less than the majority of students respondents experiencing mild stress levels. For that students are expected to manage good time and more actively inquire and learn together in relation to the density of lectures and the fufillment of the final task as an attempt to complete every task given lecturess so that the tasks of lectures and the preparation of the final task can be completed at the appointed time.